Enhancing Student Motivation and Engagement: Exploring Higher Education Students’ Experiences as Co-Creators of Curriculum - Anna Ólafsdóttir; Sólveig Zophoníasdóttir (Student Success, 2025)
This article presents a study exploring students’ experiences as co-creators of the curriculum in three master’s level courses within a teacher education programme at the University of Akureyri, a small state university in Iceland. The authors, who also oversaw the courses, adopted the principles of the Scholarship of Teaching and Learning (SoTL) to guide the research. The MUSIC model of motivation served as the analytical framework, focusing on aspects of the learning environment that foster motivation and engagement. Findings indicate that students experienced empowerment, usefulness, success, interest, and care—the core components of the MUSIC model—throughout the courses. These factors contributed to strong motivation, active engagement, and increased resilience when facing challenges. The results suggest that student involvement in curriculum design played a significant role in shaping this experience. While based on a relatively small sample, the study provides valuable insights for higher education teaching practices, both within the local context and on a global scale.